Design of Continuous Web APP: Guidance and Counseling Management Information System at SMKN 1 Purwakarta using Laravel Framework - Setyawan, Kornelius Rhesa Valdis; Rizal, Muhamad Fahmi; Widodo, Suprih; Hikmawan, Rizki (International Journal Software Engineering and Computer Science (IJSECS), 2023)
An Information System plays a crucial role in addressing the challenges associated with archiving guidance and counseling reports, thereby enhancing the quality of Guidance and Counseling Services at SMKN 1 Purwakarta. This research aims to develop a web application that not only streamlines the archiving process but also provides a foundation for future enhancements. The research process involves a comprehensive literature review, data collection, system analysis, system development, and report generation. Data acquisition encompasses both extensive literature searches and empirical fieldwork, involving interviews and direct observations of relevant stakeholders. The adoption of the Extreme Programming methodology is justified due to its efficiency in rapid software development and adaptability to changing requirements. Laravel, chosen as the framework, offers robust features, an active community, and continuous updates to support ongoing development. The outcome of this research is a Management Information System for guidance and counseling, leveraging Bootstrap for the frontend, Laravel for the backend, and MySQL for the database. The research also provides documentation for future improvements, including the results of black-box testing.